Appendiceal neuroendocrine tumour association in a patient with a large sarcomatoid renal cell carcinoma - Silva, Munasinghe; Shanmuga Anandan, Aathavan (International Surgery Journal, 2022)
Renal cell carcinoma (RCC) can develop into sarcomatoid differentiation which demonstrates aggressive biological behavior evident by the rapid progression of the tumour with multiple metastases. Though the appendiceal neuroendocrine tumour (NET) has a good prognosis, the prognosis can be worse when associated with the sarcomatoid RCC (sRCC). A 45-year-old female patient presented to the emergency department with a 2-month history of worsening right upper abdominal pain, nausea, vomiting, and significant weight loss. Computed tomography (CT) revealed heterogeneously enhancing solid cystic mass lesions arising from a lower pole of the right kidney with a tumour thrombus involving the entire right renal vein and extending into the inferior vena cava (IVC). The patient underwent radical nephrectomy and appendectomy and was managed conservatively due to the poor prognosis. After four weeks, she presented with severe right upper abdominal pain, and Magnetic resonance imaging (MRI) indicated a possible liver metastasis and tumour necrosis. In three weeks, the patient died of respiratory failure following multiple organ dysfunction syndrome (MODS). This case report outlines a presentation of sRCC with biologically aggressive disease progression and a rare association with appendiceal NET. CT, MRI, and PET scans can be helpful in the diagnosis and monitoring of disease progression. Early identification of the sRCC and appendiceal NET will contribute to better outcomes of the disease and complications. The prognostic elements and similar genetic patterns of sRCC and appendiceal NET would be of great clinical interest.